Metabolomics shows no impairment of the microenvironment of the cumulus–oocyte complex in women with isolated endometriosis. Issue 6 (December 2019) - Bouet, Pierre-Emmanuel; Chao de la Barca, Juan Manuel; El Hachem, Hady; Descamps, Philippe; Legendre, Guillaume; Reynier, Pascal; May-Panloup, Pascale
Abstract: Research question: Is there any metabolomic evidence of impairment of the cumulus–oocyte complex (COC) microenvironment in the follicular fluid of women with endometriosis? Design: A prospective observational study from January to July 2018 at the Angers University Hospital, France. Seventy-nine women undergoing IVF with or without intracytoplasmic sperm injection (ICSI) were included: 39 for endometriosis-related infertility and 40 controls with other causes of infertility. A targeted quantitative metabolomic and lipidomic analysis was performed. Results: Patient characteristics (age, body mass index, smoking status, hormonal profile and ovarian reserve markers) were comparable between the endometriosis and the control groups. There was no significant difference in the cumulative FSH dose used for stimulation between the endometriosis and the control groups (2732 versus 2257 IU, respectively). There were no differences in the oocyte maturity rates (72.2% versus 77.7%), or in the fertilization rates in IVF and ICSI (49.4% versus 50.2% and 76.4% versus 68.8%, respectively) between the endometriosis and control groups. Among the 188 metabolites analysed, 150 were accurately measured. Univariate analysis did not reveal any significant modification of metabolite concentrations, and none of the multivariate models discriminated between the two groups of patients, even when the study was restricted to the most severe form of endometriosis. Conclusions: No specific metabolomic signature of endometriosis was found in the follicular fluid of women undergoing IVF. These results suggest that there is no microenvironmental impairment of the COC in cases of isolated endometriosis among women with infertility.